Multiple capitals approach for upland agricultural systems - Mansfield, Lois (Earthscan food and agriculture., 2025)
This book focuses on upland agricultural systems and applies a multiple capitals approach to explain what they can provide at a time when many are struggling to survive.Marginal upland agricultural systems have been distorted and derailed by modern economics, politics, and the drive to intensification. This book argues for the application of a multiple capitals approach to resource management challenges for marginal upland agricultural communities. Instead of considering what upland agricultural systems lack, the book showcases how a multiple capitals framework can demonstrate the importance, interrelationships, and relevance of the suite of capitals (natural, human, social, cultural, and financial) to achieve better outcomes for upland communities, broader ecosystem services, and wider society more generally. It is designed to connect theory to practice to provide underpinning knowledge and guidance to help upland agricultural communities thrive. Drawing on case studies from the UK and Japan, as well as making comparisons with Central and South American countries, the book recommends tools for monitoring different forms of capital and suggests a management process driven by multiple capitals to create resilience in upland agricultural systems.This book will be of great interest to students and scholars of agriculture, natural resource management, ecosystem services, rural development, and those interested in applying a multiple capitals approach more widely within policy and landscape management contexts.